The Comparison of the Film Thickness and Compressive Strength Between Ariadent and Harvard Zinc Phosphate Cement. - M - Sabouhi; N Hekmat; N Baiatabadi (Isfahan University of Medical Sciences, 2005)
Introduction. Recently, the Ariadent Zinc phosphate cement has been introduced to market with low cost. Some dentists purchase this product because of low cost and others avoid buying it because of unreliable quality. The two important properties of ideal dental cement are to have the minimum film thickness (less than 25 micron) and to have favorable compressive strength. The purpose of this study was to determine the mean and to compare the film thickness and compressive strength of Ariadent and Harvard Zinc phosphate cement.Materials and Methods. In this experimental study evaluation was made based on Iranian standard number 2725. To measure film thickness of each cement, the first step was to prepare two glass slabs and their thickness was measured with micrometer, then each cement was prepared according to standard procedure and was put between the glass slabs. The difference between glass slabs with and without cement was measured. This procedure was repeated 3 times and average of three measurements were obtained and determined as mean of cement film thickness. To determine the compressive strength of each cement at first a mold was fabricated according to standard procedures. Then each prepared cement was poured in to the mold. After 24 hours each of five prepared specimens was Put under load and the average compressive strength was calculated.Results. The mean film thickness for Arident Zinc phosphate was 42.334.50 micron and for Harvard cement was 24.335.70. The mean compressive strength of Ariadent Zinc phosphate cement was 44.904.11 MPa and for Harvard cement was 62.855.19 MPa. The statistical analysis (t-student) revealed significant difference between two phosphate cement.Discussion. In this study mean film thickness of Iranian Ariadent Zinc phosphate cement was more than standard level (25 micron) and the mean compressive strength was less than standard level (70 MPa). These results indicated that Ariadent cement was of low quality and below standard. But Harvard Zinc phosphate cement had a standard film thickness and its compressive strength was close to standard and this is a reason for acceptable quality of Harvard Zinc phosphate cement.Keywords. Cement, Compressive strength, film thickness, Zinc phosphate cement